Profitability of Islamic banks: an empirical investigation of internal factors at Bank Muamalat Indonesia - Muhammad, Helmi; Rinawati, Ika (JAS (Jurnal Akuntansi Syariah), 2025)
Purpose - This research seeks to examine the impact of internal factors on the financial performance of Bank Muamalat Indonesia, a forerunner of Islamic banking within Indonesia. Method - This study adopts a quantitative approach involving secondary data from Bank Muamalat Indonesia's monthly financial statements from January 2014 to December 2023 for 120 observations. Multiple linear regression analysis was employed to investigate the relationship between a dependent variable and various independent variables. Findings - This study reveals that the CAR, RISK, and FIN variables, serving as capital adequacy, credit risk, and financing indicators, exhibit a noteworthy negative effect on profitability. In contrast, the COST and LIQ variables, which act as proxies for efficiency and liquidity, demonstrate a notable positive influence on profitability. Implications - Theoretically, this research provides a conceptual framework for comprehending the influence of internal variables on profitability via investment strategies while contributing to scientific knowledge. Practically, this research is a reference for policymakers to promote economic advancement through initiatives to enhance banking profitability.